Vol. 3 The Babylonian Esther Midrash: A Critical Commentary - Segal, Eliezer (Brown Judaic Studies, 2020)
This work, in three volumes, consists of a translation and critical commentary to folios 10b-17a of the Babylonian Talmud Tractate Megillah. The material contained therein comprises the only full midrashic exposition of an entire biblical book to have been incorporated into the Babylonian Talmud, making it the only complete midrashic work that has come down to us from that prominent Jewish community and its rabbinic teachers.